COMPUTING SUPPORT OF MATHEMATICS APPLICATIONS IN TECHNICAL EDUCATION - VAGASKÁ, Alena (Trends in education, 2008)
The paper presents the possibilities of MS Excel and Matlab program equipment utilisation with mathematics applications to engineering subjects at technical universities. The suitability of individual programs is demonstrated based on an applicable task.
Keywords: mathematics applications; technical education; MS Excel; Matlab